1995
DOI: 10.1111/j.1348-0421.1995.tb02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial‐Associated Infection with Candida albicans in Mice

Abstract: Candida yeasts are frequently isolated from patients with continuous ambulatory peritoneal dialysis peritonitis or other biomaterial‐associated infections. The mouse model of candidal peritonitis was used to study the interaction of Candida cells with end‐point attached heparinized polyethylene (H‐PE) and with polymorphonuclear leukocytes (PMNs) or macrophages (Mφ). Two Candida strains differing in cell surface hydrophobicity and in expression of fibronectin (Fn) binding were used for the study. Cells of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Candida strains derived from environmental sampling were more resistant to killing by human neutrophils than those isolated from humans or birds, but the properties of the yeasts that were associated with susceptibility and resistance were not identified 7 . A comparison of two Candida strains differing in cell surface hydrophobicity and in fibronectin (Fn) binding showed that the strain expressing a low hydrophobicity and low binding of soluble Fn was more resistant to neutrophil killing and persisted longer in i.p.‐infected mice than the strain with a higher hydrophobicity and higher binding of soluble Fn, 8 and differences in other properties, such as proteinase production, are also associated with differential susceptibility to killing by phagocytic cells 9 . However, little is known about the relative efficiency of phagocytosis and killing of various Candida isolates by neutrophils and macrophages from different inbred strains of mice and its correlation to susceptibility and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Candida strains derived from environmental sampling were more resistant to killing by human neutrophils than those isolated from humans or birds, but the properties of the yeasts that were associated with susceptibility and resistance were not identified 7 . A comparison of two Candida strains differing in cell surface hydrophobicity and in fibronectin (Fn) binding showed that the strain expressing a low hydrophobicity and low binding of soluble Fn was more resistant to neutrophil killing and persisted longer in i.p.‐infected mice than the strain with a higher hydrophobicity and higher binding of soluble Fn, 8 and differences in other properties, such as proteinase production, are also associated with differential susceptibility to killing by phagocytic cells 9 . However, little is known about the relative efficiency of phagocytosis and killing of various Candida isolates by neutrophils and macrophages from different inbred strains of mice and its correlation to susceptibility and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Reduced bactericidal activity of phagocytes has been observed following biomaterial implantation. 14,15 These phagocytosing cells have been shown to undergo an associated respiratory burst in response to a stimulus (reviewed by Rossi et al 16 ). The oxidative burst, which is characterized by the generation of reactive oxygen species (ROS) as superoxide, hydrogen peroxide, hydroxyl radicals, and singlet oxygen, has been used to test hemodialysis membrane biocompatibility in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers we showed that long‐lasting i.p. implantation of H‐PE in mice caused changes in the differentiation of bone marrow‐derived monocytes, a reduction of the bactericidal activity of phagocytes and a decrease in the host's ability to eradicate staphylococci [5–7].…”
Section: Discussionmentioning
confidence: 99%
“…As we previously demonstrated, polymorphonuclear leukocytes and macrophages from mice implanted for 2 months with heparinized polyethylene (H‐PE) showed a marked decrease in the bactericidal activity against staphylococci [5]and Candida albicans yeasts [6]. Moreover, long‐lasting implantation caused evident changes in the differentiation of bone marrow‐derived monocytes [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation